(untitled) (Journal of Pathology of Nepal, 2015)
A 16-year-old girl presented to the out patient department in Grande International Hospital with complaints of fever since 3 weeks, tonsillitis and multiple lymphadenopathy. Fine needle aspiration cytology from one of the cervical lymph nodes showed atypical lymphoid cells with prominent nucleoli in some cells; hence, a diagnosis of Non Hodgkin lymphoma was made. Bone marrow aspiration and biopsy also showed presence of similar atypical lymphoid cells. One of the lymph nodes was also excised for purpose of immunohistochemistry, and the biopsy showed effacement of lymph node architecture with diffuse proliferation of intermediate sized atypical lymphoid cells. These tumor cells showed positivity for CD3, TdT, and Ki-67. A diagnosis of T-cell lymphoblastic lymphoma was made. Lymphoblastic lymphomas are rare, accounting for 2% of all lymphomas, of which majority are of T-cell type. TCLL usually occurs in young males. In addition to lymphadenopathy, other common sites of involvement include mediastinum, CNS and bone marrow. It runs an aggressive course and overall survival of patients is poor.